Salmonella enterica species isolated from local foodstuff and patients suffering from foodborne illness: Surveillance, antimicrobial resistance and molecular detection - Z. A. AlShaheeb; Z. A. Thabit; A. G. Oraibi; A. A. Baioumy; T. G. Abedelmaksoud (Теория и практика переработки мяса, 2023)
The aim of this study was to determine the prevalence of Salmonella enterica in raw chicken meat, eggs, and ready-to-eat foods containing poultry products and among patients suffering from diarrhea as a result of ingestion of this foodborne pathogen in Baghdad, Iraq. It assesses the antibiotics susceptibility, virulence and pathogenicity of S. enterica isolates. Thirteen Salmonella spp. isolates from foodstuff and seven from clinical patients were recovered from 80 and 20 samples, respectively. Isolates from foodstuff samples displayed the highest resistance to nalidixic acid (69.23%), followed by chloramphenicol (53.84%). Salmonella spp. isolated from clinical samples showed resistance to both azithromycin and cefotaxime at the same percentage level (71.42%). The results of antibiotic resistance gene amplification (gyrA, mphA) were analyzed and showed that these genes were present in 100% and 50% of phenotypically resistant isolates, respectively. Virulence genes invA, avrA, and sipB were found on average in 86% of food isolates, accounting for 69.2%, 92.3%, and 95%, respectively. In addition, the detection of these virulence genes among clinical isolates showed their presence at the same level (85.7%). Our study revealed that unhygienic chicken slaughterhouses and lack of food safety management are strong indicators of a high probability of the Salmonella presence in our food products in the Iraqi markets.